The Impact of Poverty in Indonesia on Education - Suhendar, Fitria Arina; Sari, Ruli Vita; Pangesti, Trias; Putra, Zakiyya Muflih Gusma; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Poverty is a serious problem that Indonesia still faces. One of the concerning impacts in Indonesia is limited access to education. Economic inequality is one of the main factors in influencing poverty in Indonesia which hinders growth and affects consumption and demand. It also highlights the important role of education quality in influencing poverty status. Low access to and quality of education in poor areas are barriers to achieving social mobility and better economic opportunities. This study aims to explain the impact and cycle of poverty and how factors such as limited access to education, low levels of education, and limited access to health services can influence poverty. The research method uses a literature study approach, the data is then analyzed using qualitative methods. It can be concluded that this research provides a comprehensive picture of the problem of poverty in Indonesia, its impact, influencing factors, and steps that can be taken to overcome it. With the cooperation of various sectors and high awareness, it is hoped that efforts to reduce poverty can be successful and create a more inclusive and quality society in Indonesia.